The Influence of the Tiktok Application on Cyberbullying Behavior : Case Study: Students of SMP Negeri 5 Depok - Nur Maulidia Wati; Leliyanah; Sri Hardani (Politeknik Negeri Cilacap, 2024)
Cyberbullying is threatening, insulting, or intimidating behavior carried out through online media. This cyberbullying behavior is vulnerable to being carried out or felt by teenagers who are still easily instigated by bad actions around them. Therefore, this study aims to determine what effects the TikTok application has on cyberbullying behavior in adolescents and to find out the causes and handling solutions for cyberbullying behavior. The research was conducted using the Technology Acceptance Model (TAM) method and the descriptive quantitative method. The research was conducted from June 11 to June 21, 2024, with a sample size of 91 students determined using the proportionate stratified random sampling method. The results of hypothesis testing with the t-test state that perceived usefulness has no effect on real conditions of use, then perceived ease of use and behavior to continue using positively affect real conditions of use. Meanwhile, attitude towards use harms the real conditions of use. The f-test states that all variables have a simultaneous effect. Meanwhile, the R-Square test states that perceived usefulness, perceived ease of use, attitude towards use, and behavior to continue using contribute 62.4% to the real conditions of use